2010
DOI: 10.1088/0964-1726/19/5/055015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maleic anhydride on the damping property of magnetorheological elastomers

Abstract: In this study, maleic anhydride (MA) was selected as the compatibilizer to modify the interfaces of magnetorheological elastomers (MREs) for improving the damping property. Several samples of MREs with different contents of MA were prepared. The content of bound-rubber was measured by the extraction method. The microstructures were observed by using an environmental scanning electron microscope (SEM). The dynamic performances of these samples, including shear storage modulus, loss factor and MR effect were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…The supplements that have been applied in MREs include zinc oxide and stearic acid as activators, sulfenamide (CZ) as an accelerator, sulfur as a crosslinking agent, and mercaptobenzothiazole. The types of synthetic rubber that have been applied in MREs are styrene butadiene rubber, [169] chloroprene rubber (CIIR), [117] bromobuthyl rubber (BIIR), [170] isobutylene-isoprene, [171] cis-polyisoprene, [172] cis-polybutadiene, [173][174][175][176][177][178] acrylonitrile rubber, [47,[179][180][181] and ethylenepropylene rubber. [98] Synthetic rubber-based MREs received more attention than the natural rubber MREs since they have higher resistance to oil, better aging, and weathering as well as resilience over a wide temperature range.…”
Section: Matrix Elementsmentioning
confidence: 99%
“…The supplements that have been applied in MREs include zinc oxide and stearic acid as activators, sulfenamide (CZ) as an accelerator, sulfur as a crosslinking agent, and mercaptobenzothiazole. The types of synthetic rubber that have been applied in MREs are styrene butadiene rubber, [169] chloroprene rubber (CIIR), [117] bromobuthyl rubber (BIIR), [170] isobutylene-isoprene, [171] cis-polyisoprene, [172] cis-polybutadiene, [173][174][175][176][177][178] acrylonitrile rubber, [47,[179][180][181] and ethylenepropylene rubber. [98] Synthetic rubber-based MREs received more attention than the natural rubber MREs since they have higher resistance to oil, better aging, and weathering as well as resilience over a wide temperature range.…”
Section: Matrix Elementsmentioning
confidence: 99%
“…13 Recently, we also observed that the influence of magnetic field on the loss factor is small. 24 Therefore, the development of other methods to control the damping properties of the MREs is highly desirable. It is noted that the loss factor change of the MR gels 25 is bigger than that of the MREs 2,13,24 with increasing magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [13] and Lokander and Stenberg [9] reported the advantageously influence on the MR effect of the addition of plasticizers to the silicon rubber due to the decrease of the polymer matrix stiffness. Jiang et al [14] indicate on the positive effect of the particles surface modification on the increase of the MR effect, while Zhang et al [15], Fan et al [16] and Li et al [17] show that the enhancement of the particle-polymer matrix interaction leads to the decrease of MR effect due to the existence of bound-rubber phenomenon. The improvement of filler-matrix interaction is an effective way to improve the mechanical properties of materials; however in the case of MREs it can affect the MR effect.…”
Section: Introductionmentioning
confidence: 99%